MINAT MAHASISWA UNTUK MENJADI ANGGOTA KOPERASI MAHASISWA - Kusumantoro, Kusumantoro (Dinamika Pendidikan, 2010)
Students Cooperation (Kopma) which was still difficult to improve the welfare of its members was one factor influencing the low interest of students to be the members of Kopma. The objective of this study was to know and understand the factors that affect the interest of cooperation economics education students to become the members of Kopma.The population of the study were the 2nd semester of Cooperation Economics Education students. The data used in this research was the primary data obtained from the respondents directly. The data collections were students knowledge about Kopma, the benefits of Kopma and the Cooperation Subject. The data analysis was logit analysis with likelihood maximum method. The result of analysis using 5% significance level was that studentsâ knowledge about Kopma, the benefits of Kopma, and good understanding of Cooperative Subjects gave the positive effect to students interest to be the members of Kopma in Semarang State University (Unnes) for Cooperation Economics Education students.